2017
DOI: 10.1542/peds.2016-2730
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status, Smoke Exposure, and Health Outcomes in Young Children With Cystic Fibrosis

Abstract: ETS exposure was disproportionately high in low SES families in this cohort of children with CF. Lower SES and ETS exposure had independent adverse effects on pulmonary and nutritional outcomes. Estimated effect of SES on FEV decreased minimally after ETS adjustment, suggesting health disparity risks independent of ETS exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
48
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 44 publications
11
48
1
3
Order By: Relevance
“…Our data support recent work that demonstrated early postnatal SHSe in a murine muco-obstructive airway model alters immune function and disrupts bacterial clearance of P. aeruginosa 46. Smoke exposure has been previously shown to augment expression of MRSA virulence factors in non-CF murine models,47 48 and impact phagocytosis of P. aeruginosa in CF49 and non-CF cells in a CFTR-dependent manner 50. Early P. aeruginosa acquisition predicts long-term outcomes in children with CF,51 52 thereby predicting that detection and prevention of SHSe in young children with CF can aid in delaying establishment of certain chronic bacterial infections and subsequently worsened outcomes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our data support recent work that demonstrated early postnatal SHSe in a murine muco-obstructive airway model alters immune function and disrupts bacterial clearance of P. aeruginosa 46. Smoke exposure has been previously shown to augment expression of MRSA virulence factors in non-CF murine models,47 48 and impact phagocytosis of P. aeruginosa in CF49 and non-CF cells in a CFTR-dependent manner 50. Early P. aeruginosa acquisition predicts long-term outcomes in children with CF,51 52 thereby predicting that detection and prevention of SHSe in young children with CF can aid in delaying establishment of certain chronic bacterial infections and subsequently worsened outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, we used hair nicotine to detect SHSe, which allows for a more accurate reflection of long-term exposure. Our data are more closely aligned with recent data from the Early Pseudomonas Infection Control  (EPIC) observational study, which reported subjective SHSe in 52% of children over the 3 months prior to study inclusion 50. Regardless of reporting measure, our data suggest that young infants and children with CF are frequently exposed to tobacco products and greatly impacted by such exposures.…”
Section: Discussionsupporting
confidence: 86%
“…Further limitations of this study need to be mentioned. The impact of socioeconomic status and of the environment, for example, exposure to environmental tobacco smoke, on disease severity in CF have been described . The communal life of Hutterite families, their stable economic situation, and their strong condemnation of smoking tobacco let us assume that these risk factors are unlikely contributors to the observed disease severity in our study.…”
Section: Discussionmentioning
confidence: 93%
“…For example, in the Unite States, tobacco smoke exposure occurs most often in families with low socioeconomic status, and has independent effects on pulmonary outcomes. A recent report indicated that children exposed to tobacco smoke were more likely to have crackles and wheezes on exam . While disparities in CF lung disease related to socioeconomic status have not been explained by differential treatment of pulmonary exacerbations, the presence of these respiratory findings are associated with increased frequency of antibiotic courses .…”
Section: Discussionmentioning
confidence: 99%
“…A recent report indicated that children exposed to tobacco smoke were more likely to have crackles and wheezes on exam. 30 While disparities in CF lung disease related to socioeconomic status have not been explained by differential treatment of pulmonary exacerbations, 27 the presence of these respiratory findings are associated with increased frequency of antibiotic courses. 31 Tobacco smoke exposure is likely underreported in the CFFPR, and so we did not evaluate it in our models.…”
Section: Discussionmentioning
confidence: 99%